2016
DOI: 10.1080/23808993.2016.1174060
|View full text |Cite
|
Sign up to set email alerts
|

Personalized immunotherapy in colorectal cancer

Abstract: The fields of cancer immunology and immunotherapy have made dramatic progress in the past 20 years. Various approaches to cancer immunotherapies, including cancer vaccines using peptides, proteins, DNA, and dendritic cells, have been developed to activate antigen-specific immune cells and their efficacy has been clinically examined. Herein, we summarize previously performed clinical trials of various immunotherapies against colorectal cancer (CRC), including our own novel immunotherapeutic approach, the "perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Tumor-derived neoantigens that have not been able to stimulate the immune responses cannot induce strong immune responses in the vaccine formulation ( 180 , 181 ). Therefore, after selecting the ideal neoantigens and matching them with the patient MHC, it is necessary to evaluate the pre-existing immune responses against those neoantigens by determining the frequency of antigen-specific cytotoxic T cells (CTLs) as well as the antigen-specific IgG titer in the serum ( 15 , 182 ). Considering the pre-existing immunity in neoantigens selection could enhance the vaccination efficacy and reduce the adverse events ( 15 ).…”
Section: Personalized Immunotherapy In Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-derived neoantigens that have not been able to stimulate the immune responses cannot induce strong immune responses in the vaccine formulation ( 180 , 181 ). Therefore, after selecting the ideal neoantigens and matching them with the patient MHC, it is necessary to evaluate the pre-existing immune responses against those neoantigens by determining the frequency of antigen-specific cytotoxic T cells (CTLs) as well as the antigen-specific IgG titer in the serum ( 15 , 182 ). Considering the pre-existing immunity in neoantigens selection could enhance the vaccination efficacy and reduce the adverse events ( 15 ).…”
Section: Personalized Immunotherapy In Crcmentioning
confidence: 99%
“…Considering the pre-existing immunity in neoantigens selection could enhance the vaccination efficacy and reduce the adverse events ( 15 ). Clinical trials using this type of personalized vaccination have shown encouraging results in inducing an antitumor immune response and increasing OS even in chemoresistant CRC patients ( 178 , 179 , 182 ). The process of personalized immunotherapy in CRC is illustrated in Figure 1 .…”
Section: Personalized Immunotherapy In Crcmentioning
confidence: 99%